2004
DOI: 10.4028/www.scientific.net/msf.443-444.123
|View full text |Cite
|
Sign up to set email alerts
|

Line Broadening Analysis Using FullProf*: Determination of Microstructural Properties

Abstract: A short account of the methodology used within FullProf to extract average micro-structural properties from the analysis of broadened lines of constant wavelength diffraction patterns is presented. The approach is based on the Voigt approximation and can be combined with the Rietveld method as well as with the profile matching (Le Bail fit) procedure. Both the instrumental and sample profiles are supposed to be well described by Voigt functions. To get relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
184
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(189 citation statements)
references
References 7 publications
4
184
0
1
Order By: Relevance
“…All samples have shown strain mainly directed along c. The peak shift parameter Sh was refined according to the expression 2θ shifted = 2θ Bragg + 2Sh d 2 tan θ × 10 −2 for reflections (h,k,l) with l = 4n. Although some values obtained during this work clearly differed from zero and thus provided evidence for the existence of stacking faults [21][22][23] this parameters will not be discussed in the text. The results (cell parameters, atomic displacement parameters, grain size, strain, Sh parameter) are summarized in Table 1.…”
Section: X-ray Powder Diffraction (Equipment and Analysis)mentioning
confidence: 99%
See 1 more Smart Citation
“…All samples have shown strain mainly directed along c. The peak shift parameter Sh was refined according to the expression 2θ shifted = 2θ Bragg + 2Sh d 2 tan θ × 10 −2 for reflections (h,k,l) with l = 4n. Although some values obtained during this work clearly differed from zero and thus provided evidence for the existence of stacking faults [21][22][23] this parameters will not be discussed in the text. The results (cell parameters, atomic displacement parameters, grain size, strain, Sh parameter) are summarized in Table 1.…”
Section: X-ray Powder Diffraction (Equipment and Analysis)mentioning
confidence: 99%
“…The following microstructure parameters were extracted from the data by conventional Rietveld analyses (program Fullprof.2k [21]): average crystallite size and anisotropic strain from diffraction line broadening, and peak shift parameter Sh (related to stacking faults [21][22][23]) from the displacements of certain groups of reflections (see below). The diffraction profiles (both instrumental and sample intrinsic) were modelled by using a Thomson-Cox-Hastings pseudo-Voigt function [21] (convolutions between Gaussian and Lorentzian components having different full widths at half maximum, FWHM) to simulate the peak shapes of both NaAlH 4 , Si and impurities phases when present. Structural parameters of the alanate structure were fixed at the values reported by Hauback et al [24]: space group I4 1 /a, Na in 4a (0, 1/4, 1/8), Al in 4b (0, 1/4, 5/8) and H in 16f (0.2372, 0.3836, 0.5469).…”
Section: X-ray Powder Diffraction (Equipment and Analysis)mentioning
confidence: 99%
“…The refined lattice parameters werec ompared to those found in the literature [56,57] which showed that both materials maintained their structural characteristics after forming the nanocomposite. It is known that the polyaniline synthesis conditions interfere in their physical and chemical characteristics.…”
Section: Le Bail Methods Analysismentioning
confidence: 99%
“…The explicit formula of the intrinsic integralb readth using the SPH treatment of size broadening is given by [57]:…”
Section: Le Bail Methods Analysismentioning
confidence: 99%
“…72-0686) was refined by the Rietveld method with the FullProf.2k (v.5.40) program [14]. The microstructure of crystallites (average apparent crystallite size D, average maximum strain S) was defined within this Rietveld refinement procedure in terms of isotropic line broadening [15].…”
Section: Methodsmentioning
confidence: 99%